Effect of the atomic construction and preparation procedure on the deformation behaviour of CuZr metallic glasses. Issue 15 (13th October 2021) - Amigo, N.
ABSTRACT: The construction of metallic glasses (MGs) at the atomic scale for molecular dynamics simulations involves several factors that ultimately affect the deformation behaviour, a matter that has been rarely addressed in the literature. In order to explore this issue, 10 Cu 50 Zr 50 MGs with different random initial arrangements were subjected to compression tests under identical simulation conditions. Three different deformation behaviours were identified: weak shear band (SB) formation + homogeneous nucleation of shear transformation zones (STZs); SB formation + weak STZs nucleation; and heavily localised SB formation. Structural characterisation revealed that samples exhibiting localised SB formation presented larger populations of clusters with a high degree of local five-fold symmetry, fivefold and quasi-fivefold bonding. The deformation behaviour also varied from sample to sample when exploring other parameters such as the initial random velocities and the annealing temperature after replication of the small samples. Therefore, the preparation procedure must be considered cautiously when studying MGs ductility.